The Perfect Will of God - Weiss, G. Christian (George Christian) (Chicago Moody Publishers, 1950)
""What is God's plan for my life?"" is perhaps the most difficult question a Christian can raise. The Perfect Will of God provides guidelines for those needing help in this area. In fifteen provocative chapters, one discovers: God has a definite plan fo
Keywords: God. RELIGION -- Christian Life -- General